Comparison of different methods involved in the planning of clinical crown lengthening surgery - Zanatta,Fabricio Batistin (2010)
There is little material in the literature that compares biological width measurements in periapical and bite-wings radiographs with clinical measurements. The purpose of this study was to compare measurements of biological width taken by three different methods which are frequently used for planning periodontal surgery - periapical radiograph, bite-wing radiograph and transperiodontal probing - with the trans-surgical measurements. Thirty-four sites from twenty-one subjects were analyzed. The intra-class correlation coefficients between measurements obtained trans-surgically (gold standard) and those obtained by transperiodontal probing, periapical radiography and bite-wing radiography were determined. Average measurements were compared using the Wilcoxon test at a significance level of 0.05. Also, the frequency distribution of differences between test measurements and the gold standard was calculated. The results showed that transperiodontal probing (mean 2.05 mm) was the most accurate measurement, as compared to the gold standard (mean 1.97 mm), with no statistically significant difference observed. On the other hand, periapical and bite-wing radiographic mean values (1.56 mm and 1.72 mm, respectively) were smaller than the gold standard, with statistically significant differences (p < 0.05). It was concluded that transperiodontal probing was the most accurate measurement, as compared to the gold standard, followed by that obtained with the bite-wing radiograph. The clinical relevance of these results could be that planning for crown lengthening surgery should, preferably, include transperiodontal probing.